Comparison of mucosal microbiota populations across the gastrointestinal tract of healthy dogs - Ching-Yen Lin; Tzu-Wen L. Cross; Kelly S. Swanson (Animal Microbiome)
Abstract The gastrointestinal (GI) microbiota plays a crucial role in host health and disease in dogs, but the knowledge regarding the mucosal associated microbiota along the GI tract is limited in dogs. Therefore, the objective of this study was to characterize the phylogeny and predicted functional capacity of microbiota residing on the gut mucosa across five GI regions of healthy young adult and geriatric dogs fed different diets. Twelve weanling (8 weeks old) and 12 senior (11.1 years old) beagles were randomly assigned to be fed an animal product-based diet or plant product-based diet for 12 months. At that time, mucosal samples from the stomach, duodenum, jejunum, ileum, and mid-colon were collected. DNA was extracted and the hypervariable region 4 (V4) of the 16S rRNA gene was amplified to assess microbiota using Illumina MiSeq sequencing. Data were analyzed using QIIME 1.9.1. and Statistical Analyses of Metagenomic Profiles software 2.1.3. Gene predictions were made using Phylogenetic Investigation of Communities by Reconstruction of Unobserved States. Taxonomic assessment revealed a greater (p < 0.05) species richness in the mid-colon compared with other segments. Principal coordinates analysis of weighted UniFrac distances demonstrated distinct clusters of stomach, ileum, and mid-colon samples, indicating the presence of unique microbial communities in these regions. The predominant phyla in all five segments were Proteobacteria, Firmicutes, Bacteroidetes, Actinobacteria and Fusobacteria, but their relative abundances varied between segments. Proteobacteria had a decreasing relative abundance from the stomach to mid-colon (q < 0.05). The ileum had the highest while the stomach had the lowest relative abundance of Firmicutes (q < 0.05). The duodenum had a higher abundance of Bacteroidetes than the stomach and ileum (q < 0.05). The mid-colon had a higher Fusobacteria relative abundance than other regions (q < 0.05). The predicted functional capacities of the microbiota in the stomach differed from those in the other segments. Age and diet of dog did not significantly impact the taxonomy or predicted functional capacities of the mucosal microbiota. In conclusion, our findings demonstrate distinct characteristics of the mucosal microbiota across various segments of canine GI tract.